Influence of the Architecture and Interfaces in Perovskite Solar Cells (2017)
ABSTRACT: Perovskite solar cells (PSCs) have reached a surprising high performance in the last few years due to the large research e ort. Some of this e ort has focused on optimizing the architecture, selective layer properties, and the interaction between the di erent components of the cell. Nevertheless, the e ect of the architecture and selective layers on some physical properties of the perovskite itself, and in the complete cell has not been completely understood. Moreover the improvement of the carrier dynamics at the interface and through di erent surface treatment is one most interesting topic in the PSCs community. In this work, I present a study of the in uence of the architecture, selective layers, and interfaces treatments in metal halide PSCs. In order to analyze the in uence of the architecture and di erent selective contacts, rst it was implemented di erent hole transporting layers (HTL). To do that, was studied the in uence of nickel oxide (NiOx), copper thiocyanate (CuSCN) and copper oxide (CuOx) in a planar structure. The PSCs with NiOx presented superior performance than the PSCs with CuOx and CuSCN. Their performance (solar cells with CuSCN and CuOx) was similar to the cells without HTL. The low photovoltaic response of the cells with CuOx CuSCN as HTL was due to poor morphology, bad transport properties, and de cient band alignment with perovskite. In another way, the band alignment, high coverage area, and good morphology make the cells fabricated with NiOx superior. Afterward di erences in the band bending and work function of the perovskite as is grown on NiOx in planar architecture or NiOx-Al2O3 in a mesoporous con guration were obtained. A facet dependence on the photoluminiscence (PL) and lifetime of the charges through Scanning Intensity modulated kelvin probe microscopy (IM-KPFM) was obtained. The in uence of the surface modi cations in selective layers in perovskite solar cells were worked in three cases. In rst instance the role of rhodamine interface between the 61-butyric acid methyl ester (PCBM) and the Ag electrode was carefully studied. Through kelvin Probe force microscopy (KPFM) was found a attening of the PCBM surface after rhodamine treatment, and a change in the Ag electrode work function after its interaction with the rhodamine. As a consequence the ll factor (FF) and the short circuit current (Jsc) increase and the performance of the cells was improved. iii As another example of interface modi cation, a nanoparticle-based solution-processed TiO2 layer (TiO2-NP) was implemented. I studied the in uence of TiO2- PCBM treatment in a n-i-p solar cell. Through SKPFM I found a band bending present in an p-i-n structure without PCBM which means that TiO2-NP layer does not block the holes in the lm due to pinholes in the lms, meanwhile after the PCBM treatment the band bending changes the direction, and the performances of the PSCs is improved signi cantly. Additionally, I analyzed the in uence of MACl treatment in a scalable process for perovskite fabrication based on the acetonitrile crystallization route (ACN). Using surface photovoltage (SPV) was studied the change in morphology and electronic properties of the ACN perovskite when MACl treatment is implemented. I found that after MACl treatment, grain size changes, and a passivation of the boundaries under illumination, moreover the PL response is clearly superior with MACl, proving the increase of the radiative recombination, and a decrease of trap states assisted recombination. Those results explain the improvement of all the photovoltaic parameters and performance of the PSCs when the perovskite is fabricated through the ACN route under MACl treatment.